COVID-19 Malaysia overview: evaluate driving awkward posture and muscle fatigue through RULA and Electromyography (EMG) analysis on health problem among older taxi drivers - Md Yusoff, Irwan Syah; Mohd Tamrin, Shamsul Bahri; Norjali Wazir, Mohd Rozilee Wazir (UPM Press, 2022)
Driving taxis is one of the alternative jobs older people took up during the COVID-19 pandemic. This study evaluated driving posture and muscle fatigue among older taxis drivers in Malaysia during COVID-19 using Rapid Limb Assessment and Electromyography. The Rapid Upper Limb Assessment questions were used to assess awkward driving posture and Electromyography to measure muscular fatigue. RULA analysis body score at value score 7 (23.5%)- required change immediately and value score 5/6 (61.9%) - required investigation and change soon. There is a significant decrease in energy (p<0.05) on EMG analysis. Ergonomic education on driving posture may improve the lifestyle and well-being of older Malaysian taxis driver.